Endoscopic-Assisted Burr Hole Reservoir and Ventricle Catheter Placement - Antes, Sebastian; Tschan, Christoph A.; Heckelmann, Michael; Salah, Mohamed; Senger, Sebastian; Linsler, Stefan; Oertel, Joachim (World Neurosurgery, 2017)
Background Accurate positioning of a ventricle catheter is of utmost importance. Various techniques to ensure optimal positioning have been described. Commonly, after catheter placement, additional manipulation is necessary to connect a burr hole reservoir or shunt components. This manipulation can lead to accidental catheter dislocation and should be avoided. Here, we present a new technique that allows direct endoscopic insertion of a burr hole reservoir with an already mounted ventricle catheter. Methods Before insertion, the ventricle catheter was slit at the tip, shortened to the correct length, and connected to the special burr hole reservoir. An intracatheter endoscope was then advanced through the reservoir and the connected catheter. This assemblage allowed using the endoscope as a stylet for shielded ventricular puncture. To confirm correct placement of the ventricle catheter, the endoscope was protruded a few millimeters beyond the catheter tip for inspection. Results The new technique was applied in 12 procedures. The modified burr hole reservoir was inserted for first-time ventriculoperitoneal shunting (n = 1), cerebrospinal fluid withdrawals and drug administration (n = 2), or different stenting procedures (n = 9). Optimal positioning of the catheter was achieved in 11 of 12 cases. No subcutaneous cerebrospinal fluid collection or fluid leakage through the wound occurred. No parenchymal damage or bleeding appeared. Conclusions The use of the intracatheter endoscope combined with the modified burr hole reservoir provides a sufficient technique for accurate and safe placement. Connecting the ventricle catheter to the reservoir before the insertion reduces later manipulation and accidental dislocation of the catheter.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Burr hole reservoir; Intraventricular stenting; Neuroendoscopy; Shunt scope; Ventricle catheter placement